Continuous Separation Process of Water-in-Crude Oil Emulsion by Simultaneous Application of an Electrical Field Combined with a Novel Absorbent Based on Functionalised PolyHIPE Polymer - Algburi, Abbas K. (Journal of Petroleum Research and Studies, 2021)
During the extraction process of crude oil, the removal of water from a high stability water-in-crude oil emulsions is life-threatening for the production of a profitable product. However, several technologies of separation exist today, e.g. stripping columns, centrifugal separators, coalescence separators, vacuum distillation systems and gravity separators, almost all of these approaches are not able to completely remove water from water-in-crude oil emulsions besides their high cost. In this study, the preparation of a high internal phase emulsion (HIPE) was achieved on a laboratory scale. Subsequently, it was polymerized and sulphonated to produce a hydrophilic macroporous polyHIPE polymer (PHP) called silane (vinyl trimethoxy silane) PHP with a relatively high surface area of 104 m 2/g. It demonstrates high water absorption capability in addition to its ability to remove surface active substances such as Mg, Ca, Na and Cl, from crude oil which cause crude oil emulsification. The rates of demulsification of water-in-crude oil emulsions were examined in high AC field under various emulsion inlet flow rates from 100 ml/min to 1500 ml/min and different applied voltages from 1-5 kV (equivalent to 14-69 kV/m) by using a model of an electrostatic separator combined with silane PHP as absorber. It was found that the best separation efficiency was 91% with applied voltage of 5 kV and emulsion inlet flow rate of 100 ml/min. When the spent silane PHP was reused in the demulsification process under similar conditions, a separation efficiency of up to 73% was achieved. Also, it was noticed that the separation efficiency was increased with the increase in applied voltage and reduction in the inlet flow rate of emulsion. Moreover, the original or spent silane PHP were able to remove the undesired metals present in the crude oil. Keywords: Demulsification; Emulsion flow rate; Separation efficiency; Electrostatic Separator; Electric field strength.